Genome-wide DNA methylation changes in two Brassicaceae species sampled alongside a radiation gradient in Chernobyl and Fukushima. (December 2018) - Horemans, Nele; Nauts, Robin; Vives i Batlle, Jordi; Van Hees, May; Jacobs, Griet; Voorspoels, Stefan; Gaschak, Sergey; Nanba, Kenji; Saenen, Eline
Abstract: The long-term radiological impact to the environment of the nuclear accidents in Chernobyl and Fukushima is still under discussion. In the course of spring of 2016 we sampled two Brassicacea plants, Arabidopsis thaliana and Capsella bursa-pastoris native to Ukraine and Japan, respectively, alongside a gradient of radiation within the exclusion and difficult to return zones of Chernobyl (CEZ) and Fukushima (FEZ). Ambient dose rates were similar for both sampling gradients ranging from 0.5 to 80 μGy/h at plant height. The hypothesis was tested whether a history of several generations of plants growing in enhanced radiation exposure conditions would have led to changes in genome-wide DNA methylation. However, no differences were found in the global percentage of 5-methylated cytosines in Capsella bursa pastoris plants sampled in FEZ. On the other hand a significant decrease in whole genome methylation percentage in Arabidopsis thaliana plants was found in CEZ mainly governed by the highest exposed plants. These data support a link between exposure to changed environmental conditions and changes genome methylation. In addition to methylation the activity concentration of different radionuclides, 137 Cs, 90 Sr, 241 Am and Pu-238, 239, 240 for CEZ and 137, 134 Cs for FEZ, was analysed in both soil and plant samples. The ratio of 5.6 between 137 Cs compared to 134 Cs was as expected five years after the FEZ accident. For CEZ 137 Cs is the most abundant polluting radionuclide in soil followed by 90 Sr. Whereas 241 Am and Pu-isotopes are only marginally present. In the plant tissue, however, higher levels of Sr than Cs were retrieved due to a high uptake of 90 Sr in the plants. The 90 Sr transfer factors ranged in CEZ from 5 to 20 (kg/kg) depending on the locality. Based on the activity concentrations of the different radionuclides the ERICA tool was used to estimate the total dose rates to the plants. It was found that for FEZ the doses was mainly contributable to the external Cs-isotopes and as such estimated total dose rates (0.13–38 μGy/h) were in the same range as the ambient measured dose rates. In strong contrast this was not true for CEZ where the total dose rate was mainly due to high uptake of the 90 Sr leading to dose rates ranging from 1 to 370 μGy/h. Hence our data clearly indicate that not taking into account the internal contamination in CEZ will lead to considerable underestimation of the doses to the plants. Additionally they show that it is hard to compare the two nuclear accidental sites and one of the main reasons is the difference in contamination profile. Highlights: For Fukushima, Capsella plants did not show differences in genome wide methylation levels contributable to radiation level. A decrease in whole genome wide methylation with increasing dose rate was found for Arabidopsis plants from Chernobyl. Compared to Cs, Am and Pu isotopes high transfer factors for Sr were found for Arabidopsis plants in Chernobyl. Total dose rates (external plus internal) differ considerably between the two sites despite similar ambient dose rates.